ANALYSIS OF FEASIBILITY OF THYLAPHIA FISH CULTIVATION AT FLOATING NET CAGES IN TANJUNG BUNGA VILLAGE, SUB-DISTRICT PANGURURAN SAMOSIR REGENCY - Rizal Damanik; Hendrik Hendrik; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was carried out on 1 until 11 August 2018 in Tanjung Bunga Village, Pangururan District, Samosir Regency. The purpose of this study was to determine how much investment and income costs, analyze how business feasibility is reviewed based on the investment criteria of the KJA business with Scale I, namely 10 cages, Scale II 20 cages, and Scale III 30 cage bags. This study also aims to see how the sensitivity of KJA business is seen from the investment criteria The results showed that the total investment for the KJA Scale I business was IDR. 262.798.000, Scale II was IDR. 492,450,000 and Scale III was IDR. 752,890,000. Whereas for income per year or 2 times the production period for KJA business on a scale I is IDR 163,344,000, and for scale II is IDR.380,000,000 and scale 3 is IDR. 547,400,000. Based on the results of the calculation of investment criteria obtained, the NPV value of KJA scale I business is IDR. 499.702.702 and the scale II business is IDR. 1,364,825,240 and the scale III business is IDR. 1.919.739.480 for 10 years. BCR for scale I is 1.21, and KJA scale II was 1.31, and KJA scale III was 1.34. KJA business IRR scale I is 48,5% and scale II is 50,8% and business scale III is 51,2%. (IRR> i), meaning that the IRR value is greater than the highest interest rate per year. From the results of the calculation of sensitivity analysis within 10 years of the three types of KJA business scale, it can be concluded that the KJA business will experience a loss if there is an increase in cost (cost) of 10% and production has decreased by 10% in the fourth scenario. Where the NPV value of the three business scales is still positive, BCR is <1, and the IRR is smaller than the highest interest rate per year, then the business is better stopped if the KJA business experiences something like this. Keywords: Floating Net Investment, Investment, Business Analysis, Sensitivity Analysis.